El otorgamiento de la licencia para la explotación minera y su contribución a la comisión del delito de usurpación agravada - Lozano Broca, Julia Beatriz (2017)
ABSTRACT This study of Constitutional Law, whose main objective is to prevent the violation of fundamental rights of the people living in the highlands of the Department of La Libertad, in the cities of Otuzco, Huamachuco, Santiago de Chuco and Julcán, who They engaged in small-scale agriculture and are affected by the development of formal mining. 12 records on complaints of usurpation, interviews: 10 prosecutors, 10 judges, 10 lawyers, 10 teachers and 20 local residents the causes of the usurpation Aggravated in this mining in the Sierra Liberteña, taking as sample development is analyzed. Deductive methodology applied to this sample leads us to identify the causes of the usurpation aggravated incurred by mining companies on agricultural land and often intangible areas of the Sierra de La Libertad, in order to prevent and avoid social conflicts in which the fundamental rights of peasants are violated and collide with constitutional precepts. This research concludes that the factors that allow the usurpation aggravated formal mining on agricultural land of the people of the highlands of the Department of La Libertad are legal, political, economic, social order and historical, for the interest and overprotection that the state gives to mining activity to the detriment of the fundamental rights of peasants who develop agricultural and livestock activity and paradoxically live in extreme poverty.